Interventions for giggle incontinence: A scoping review of therapeutic strategies and outcomes. - Bhavsar, Rutuben Harshadbhai; Malik, Kritagya R.; Kumar, Palani G. (Indian Journal of Urology)
Background: Giggle incontinence (GI) is a rare type of urinary incontinence that affects children and adolescents, impacting their quality of life by causing social isolation, reduced self-confidence, and low self-esteem. To counteract the symptoms of GI, various treatment approaches have been described, but there is a dearth of reporting on their effectiveness. Objective: This review aims to synthesize evidence on the management of GI in the adolescent population, focusing on pharmacological and nonpharmacological interventions. Methods: Ascoping review was conducted using the Joanna Briggs Institute methodology and Preferred Reporting Items for Systematic Reviews and Meta-analyses extension for scoping reviews guidelines, along with the Population, Concept, Context framework, to perform a comprehensive search across major databases and gray literature. Treatment outcomes and follow-up data were extracted. Results: Of the 72 records, 9 studies met the inclusion criteria, in which the commonly used interventions were pharmacologic (mainly methylphenidate [MPH]) and nonpharmacologic (biofeedback, behavioral modifications). Studies explored the effectiveness of these interventions and found positive outcomes. Follow-up showed a significant effect of both the types of interventions. Conclusions: GI remains under-recognized in the adolescent population despite its effects on psychological and urological health. A multidisciplinary approach targeting the GI can help improve outcomes. This review provides insights about the use of various nonpharmacological therapies, such as biofeedback and behavioral therapy, and pharmacological therapies in the form of MPH to improve GI. Nonpharmacological approaches are low-risk and can be adapted as the primary treatment. Future research with planned methodology to compare the treatment efficacy is needed to improve the outcomes.